USE OF DIDACTIC GAMES IN FOREIGN LANGUAGE TEACHING - Islambayeva Klara Jo‘raboyevna (American Journals Publishing, 2023)
In this article, opinions were expressed about the use of didactic games in teaching a foreign language.
Keywords: foreign language, communication, conditions, education, ICT, intensive, extensive, practical.